Hemodynamic status during endovascular stroke treatment: association of blood Pressure with functional outcome - Chen, Min; Kronsteiner, Dorothea; Pfaff, Johannes; Jäger, Laura Bettina; Bendszus, Martin; Kieser, Meinhard; Möhlenbruch, Markus Alfred; Ringleb, Peter A.; Bösel, Julian; Schönenberger, Silvia (Neurocritical care, 2021)
Optimal blood pressure (BP) management during endovascular stroke treatment in patients with large-vessel occlusion is not well established. We aimed to investigate associations of BP during different phases of endovascular therapy with reperfusion and functional outcome.